Subtitling Strategies: A Case of Indah Asmigianti on OmeTV - Nurul Huda Ahmad Hasibuan; Siti Aisyah Ginting; Meisuri Meisuri (RIRAI Publisher, 2023)
Subtitling strategies used by subtitlers in translating words, phrases, and speaker’s utterances in the audiovisual field. The aim of this study was to analyze the types of subtitling strategies used by Indah Asmigianti on OmeTV. It adopted a descriptive qualitative method. The subject of the study was the video of Indah Asmigianti taken on YouTube in January 2023, complete with subtitles. The focus was on the conversation between Indah Asmigianti and strangers. The subtitling strategies were categorized according to Gottlieb's theory (1992). The result revealed eight types of subtitling strategies used, namely: paraphrase (33.2%), transfer (22.1%), condensation (11%), expansion (8%), deletion (5.3%), imitation (5%), resignation (4.2%), and decimation (3.2%). Transcription and dislocation strategies were not found in this research. The most frequently used strategy was paraphrase. This research contributes to understanding the complexity of subtitling as a form of cultural translation.